PENGARUH KONSUMSI DAN HARGA DAGING SAPI TERHADAP PENDAPATAN RUMAH POTONG HEWAN SIMPANG RIMBO KELURAHAN KENALI BESAR KECAMATAN ALAM BARAJO (Jurnal Riset Manajemen dan Akuntansi, 2023)
This study aims to determine the effect of beef consumption and beef prices on the income of the Simpang Rimbo slaughterhouse. This research is a quantitative type. The samples used were 36 types of secondary data. Based on the results of the study, there was one variable that did not significantly influence the income of the Simpang Rimbo slaughterhouse, namely the price of beef, while the other variable, namely beef consumption, had a positive and significant effect on the income of the Simpang Rimbo slaughterhouse. Simultaneously there is a significant influence between beef consumption and beef price. The Adjusted R Square (R2) value is 0.411 or 41.1%, which means that the influence of the independent variable on the dependent variable has an effect of 41.1% and the remaining 58.9% is influenced by other variables outside this study